2016
DOI: 10.15288/jsad.2016.77.464
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Effects of Early Childhood Maltreatment on Co-Occurring Substance Misuse and Mental Health Problems in Adulthood: The Role of Adolescent Alcohol Use and Depression

Abstract: ABSTRACT. Objective: This study tested a developmental model in which subtypes of childhood maltreatment were hypothesized to have direct and indirect effects on co-occurring depression, anxiety, and substance misuse in adulthood. Indirect effects involved adolescent alcohol use and depression, which were included as mediators in the tested models. Method: This prospective longitudinal study (N = 332; 52.4% male) followed the participants from childhood (18 months to 6 years of age) to adulthood (31-41 years o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
3
3

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(20 citation statements)
references
References 28 publications
0
15
0
5
Order By: Relevance
“…A recent study reported that depression mediates the relationship between childhood maltreatment and alcohol abuse [156]. Another study recently reported that sexual abuse increases alcohol use and depression in adolescence, which then influenced risk for adult depression, anxiety, and substance abuse [157]. In a longitudinal study investigating changes in patterns of substance use over time in 937 adolescents, childhood maltreatment increased progression toward heavy polysubstance use [158].…”
Section: Pathways To Mood Disorder Outcomes-more Work On Mechanisms Amentioning
confidence: 99%
“…A recent study reported that depression mediates the relationship between childhood maltreatment and alcohol abuse [156]. Another study recently reported that sexual abuse increases alcohol use and depression in adolescence, which then influenced risk for adult depression, anxiety, and substance abuse [157]. In a longitudinal study investigating changes in patterns of substance use over time in 937 adolescents, childhood maltreatment increased progression toward heavy polysubstance use [158].…”
Section: Pathways To Mood Disorder Outcomes-more Work On Mechanisms Amentioning
confidence: 99%
“…Traumatized children are more likely than other children to exhibit a wide range of adverse health behaviors that can impact their everyday life, including those that increase their risk of adolescent pregnancy. These include earlier sexual debuts, a greater number of sexual partners, reduced use of contraception, and increased use of alcohol . Therefore, it is understandable why other research has found that experiencing child sexual abuse more than doubles females' odds of adolescent pregnancy …”
Section: Literature Reviewmentioning
confidence: 99%
“…Another reason is because of the wide‐ranging impact of trauma on developmental processes that can impact many aspects of health and functioning including mental health, ability to learn, coping with everyday problems, and developing and maintaining relationships (eg, some survivors of childhood sexual abuse report problems with low sexual interest and few close relationships, while others display high‐risk sexual behaviors and promiscuity) . In addition, traumatized youth are at increased risk for a wide range of health behaviors that increase the risk of adolescent pregnancy . Finally, school‐based pregnancy prevention programs include explicit discussion of sexuality and related topics that can serve as trauma triggers to sexual violence survivors.…”
Section: Implications For School Healthmentioning
confidence: 99%
“…However, much of the research on childhood maltreatment has either failed to distinguish between different forms of maltreatment or has focused on a single form of maltreatment without consideration of overlap with other types. 9 There is also considerable heterogeneity in how the exposure to trauma is measured across studies. In adult studies, childhood maltreatment is often measured by retrospective self-report where issues of bias 10 and omission 11 can confound accuracy.…”
mentioning
confidence: 99%